2020
DOI: 10.1038/s41467-020-14447-1
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake slip surfaces identified by biomarker thermal maturity within the 2011 Tohoku-Oki earthquake fault zone

Abstract: Extreme slip at shallow depths on subduction zone faults is a primary contributor to tsunami generation by earthquakes. Improving earthquake and tsunami risk assessment requires understanding the material and structural conditions that favor earthquake propagation to the trench. We use new biomarker thermal maturity indicators to identify seismic faults in drill core recovered from the Japan Trench subduction zone, which hosted 50 m of shallow slip during the M w 9.1 2011 Tohoku-Oki earthquake. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…This greatly reduces the diffusion time compared to previous models (Saffer & Bekins, 1998, 1999) which attribute all the geochemical anomalies to episodic fluid flow and consider a single thick fault strand. Also, our results of frequently active fault strands are in line with studies on biomarker thermal maturity indicators that identified seismic faults in drill cores recovered from the Japan Trench subduction zone (Rabinowitz et al., 2020). These results show that even fault zones that have hosted earthquakes with displacement ≥10 m ruptured repeatedly during a period of 36 kyrs.…”
Section: Discussionsupporting
confidence: 90%
“…This greatly reduces the diffusion time compared to previous models (Saffer & Bekins, 1998, 1999) which attribute all the geochemical anomalies to episodic fluid flow and consider a single thick fault strand. Also, our results of frequently active fault strands are in line with studies on biomarker thermal maturity indicators that identified seismic faults in drill cores recovered from the Japan Trench subduction zone (Rabinowitz et al., 2020). These results show that even fault zones that have hosted earthquakes with displacement ≥10 m ruptured repeatedly during a period of 36 kyrs.…”
Section: Discussionsupporting
confidence: 90%
“…Biomarker thermal maturity has proven an effective tool for identifying zones of coseismic slip within a fault zone (Coffey et al., 2019; Polissar et al., 2011; Rabinowitz et al., 2020; Savage & Polissar, 2019; Savage et al., 2014). Biomarkers are the molecular remains of organisms preserved in sedimentary rocks, which when heated, undergo structural changes, rearrangements, or transformations depending upon the thermal stability of the molecules.…”
Section: Background and Methodsmentioning
confidence: 99%
“…A possible mechanism for such a local temperature elevation could be flash heating due to friction on the fault plane. Frictional heating is known to occur on fault planes (Goldsby and Tullis, 2007;Smith et al, 2015), particularly in episodes of rapid seismic slip (Rabinowitz et al, 2020). However, the magnitude and duration of elevated temperatures from friction depend on a range of factors such as permeability, slip duration, and fault thickness (Bustin, 1983;Mase and Smith, 1987;Fulton and Harris, 2012;Kitamura et al, 2012), and there is therefore uncertainty as to whether this would always be sufficient to alter the Raman spectra.…”
Section: I[d]/i[g]mentioning
confidence: 99%